Dissolved Oxygen Balance Model for Neris - Gaudenta (Nonlinear Analysis: Modelling and Control, 2001)
We consider a dissolved oxygen balance model for Neris, which includes biochemical oxygen demand, nitrification, sedimentation, algae respiration and photosynthesis. The load from point sources, tributaries and distributed sources are taken into account. Long-term systematic components such as drift and seasonal components are analysed by applying time series analysis.The model is adapted according to the State Environmental Monitoring, and source data of controlled pollution covering the period 1978-1998.
Keywords: water pollution; dissolved oxygen; modelling; time series analysis